Free-Boundary Seepage from Asymmetric Soil Channels - Adrian Carabineanu (International Journal of Mathematics and Mathematical Sciences)
We present an inverse method for the study of the seepage from soil channels without lining. We give integral representations of the complex potential, velocity field, stream lines, free phreatic lines, and contour of the channel by means of Levi-Civitá's function ω. For different values of the Taylor coefficients of ω, we calculate numerically the contour of the channel, the phreatic lines, the seepage loss, the velocity field, the stream lines, and the equipotential lines. Examples are given for various symmetric or asymmetric channels, with smooth contours or with angular points.